Plant aquaporins alleviate drought tolerance in plants by modulating cellular biochemistry, root‐architecture, and photosynthesis. Issue 2 (19th January 2021) - Patel, Jaykumar; Mishra, Avinash
Abstract: Water is a vital resource for plants to grow, thrive, and complete their life cycle. In recent years, drastic changes in the climate, especially drought frequency and severity, have increased, which reduces agricultural productivity worldwide. Aquaporins are membrane channels belonging to the major intrinsic protein superfamily, which play an essential role in cellular water and osmotic homeostasis of plants under both control and water deficit conditions. A genome‐wide search reveals the vast availability of aquaporin isoforms, phylogenetic relationships, different families, conserved residues, chromosomal locations, and gene structure of aquaporins. Furthermore, aquaporins gating and subcellular trafficking are commonly controlled by phosphorylation, cytosolic pH, divalent cations, reactive oxygen species, and stoichiometry. Researchers have identified their involvement in regulating hydraulic conductance, root system architecture, modulation of abiotic stress‐related genes, seed viability and germination, phloem loading, xylem water exit, photosynthetic parameters, and post‐drought recovery. Remarkable effects following the change in aquaporin activity and/or gene expression have been observed on root water transport properties, nutrient acquisition, physiology, transpiration, stomatal aperture, gas exchange, and water use efficiency. The present review highlights the role of different aquaporin homologs under water‐deficit stress condition in model and crop plants. Moreover, the opportunity and challenges encountered to explore aquaporins for engineering drought‐tolerant crop plants are also discussed here.